2014
DOI: 10.1007/s11525-014-9249-5
|View full text |Cite
|
Sign up to set email alerts
|

Surviving truncation: informativity at the interface of morphology and phonology

Abstract: When disyllabic words of Chinese are compounded, truncation often applies to yield a disyllabic output that draws one syllable from each of the contributing words, e.g., xiàdiē + fúdù → xiàdiē + fúdù → diēfú. A substantial portion of new words enter Chinese via this process, and all combinations of four underlying syllables are attested in disyllabic neologisms. Variation in which syllable of the base escapes truncation has been described as arbitrary, but our analysis uncovers a clear pattern. Informative syl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Although this proposal may seem rather radical, it did not come out of the blue- Vance (2007; repeatedly drew attention to the relevance of Japanese orthography in the patterning of rendaku, as we will see below in section 3.1. This proposal is also inspired by other work showing the interplay between orthographic and linguistic knowledge in shaping our phonological behaviors, which was reviewed in the introduction of this paper (Poser 1990;Nagano & Shimada 2014;Shaw et al 2014; see also Taft 2006).…”
Section: The Current Case Study: Rendakumentioning
confidence: 86%
See 4 more Smart Citations
“…Although this proposal may seem rather radical, it did not come out of the blue- Vance (2007; repeatedly drew attention to the relevance of Japanese orthography in the patterning of rendaku, as we will see below in section 3.1. This proposal is also inspired by other work showing the interplay between orthographic and linguistic knowledge in shaping our phonological behaviors, which was reviewed in the introduction of this paper (Poser 1990;Nagano & Shimada 2014;Shaw et al 2014; see also Taft 2006).…”
Section: The Current Case Study: Rendakumentioning
confidence: 86%
“…At the same time though, this hypocoristic formation pattern is based on a bimoraic foot in that the outcome of the conversion is bimoraic (Poser 1990), as is the case with the argot pattern discussed by . Shaw et al (2014) found something essentially similar in Chinese: in order to account for compound truncation patterns in Chinese, it is crucial to consider Chinese characters as part of lexical representations. Shaw et al (2014) demonstrate that what survives in truncation is affected by the predictability of each compound member, and that "predictability" is arguably a crucial part of our linguistic knowledge (Hall et al 2016 for a recent overview).…”
Section: Theoretical Contextmentioning
confidence: 96%
See 3 more Smart Citations